The Effects of Perceived Supervisor Support and Servant Leadership on Voluntary Turnover - Purba, Debora Eflina; Fawzi, Ahmad Raldiano (Bina Nusantara University, 2019)
This research aimed to investigate the predictive validity of perceived supervisor support and servant leadership on voluntary turnover. Data were taken from employees and ex-employees of five batches of the development program in a company in Jakarta, Indonesia (N = 92). The data were analyzed using a logistic regression technique on Statistical Packages for Social Sciences (SPSS) software. The results show that both perceived supervisor support and servant leadership are negatively related to voluntary turnover. The servant leadership accounts for more variance on voluntary turnover and perceived supervisor support. The theoretical and practical implications of the findings are further discussed.